New solutions for the generalized resonant nonlinear Schrodinger equation - Nisar, Kottakkaran Sooppy; Ali, Khalid K.; İnç, Mustafa; Mehanna, M. S.; Rezazadeh, Hadi; Akinyemi, Lanre (Elsevier, 2022)
The resonant nonlinear Schrodinger's equation portrays the wave propagation in fiber optics. In this work, we get new solutions using two powerful and effective analytical methods, namely: The Bernoulli sub-ODE method and the (G '/G)-expansion method. Moreover, we illustrate our results with some graphs.
Keywords: rNLSE; BSODEM; Soliton solution; Finite difference method